Analytical modeling of orthogonal spiral structures. (7th October 2016) - Santos, Auteliano A; Hobeck, Jared D; Inman, Daniel J
Abstract: This paper presents the analytical modeling of orthogonal spiral structures (OSS), a promising option for small-scale energy harvesting applications. This unique multi-beam structure is analyzed using a distributed parameter approach with Euler–Bernoulli assumptions. First, an aluminum substrate is evaluated to determine if the proposed design can be used to capture vibration energy in the desired frequency range using a twelve beam OSS. Finite element calculations are used to validate the analytical model. This model is then modified to include the electromechanical effects of a piezoelectric layer added to the aluminum substrate. Lastly, the effects of the beam width and the number of beams is analyzed for a particular surface area of the OSS. Results show that increasing the number of beams causes a reduction in the first natural frequency. From those results, it is possible to conclude that OSS can be used as an alternative to current energy harvesting systems for MEMS applications, allowing the capture of environmental energy in the frequency range of common mechanical systems.